Analgesic Activity of Ethanolic Corn Silk Extract (Zea mays L.) - Nurlaili Saniyyah; Andri Tilaqza; Zainul Fadli (Nusantara Science and Technology Proceedings, 2023)
Zea mays Corn silk is an herbal plant that is used empirically to relieve pain. Corn silk is known to have alkaloid compounds (trigonelline and indole) and flavonoids (vitexine and apigenidine) that have potential analgesic effects. On the official website of Prediction of Activity Spectra for Substances (PASS), it is known that indole is useful as a cyclooxygenase and prostaglandin synthase inhibitor. This study aims to determine the analgesic activity of 70% Ethanolic corn silk (Zea mays L) extract using a rendal-selitto analgesimeter. The extract was evaluated at 125, 250, and 500 mg/kg BW. The positive control groups were treated with Mefenamic Acid 45 mg/kgBW, and CMC Na 0,5% suspension was given to negative control. All treatment administrations were performed orally. Pain threshold was evaluated with Ugo-Basil analgesimeter and analgesic activity was calculated with percent inhibition of analgesic. The percent pain inhibition of Ethanolic corn silk (Zea mays L) extract 125, 250 and 500 mg/kg BW were about 23.71%, 28.08%, and 33.83% compared to mefenamic acid 27,55%. The 500mg/kg BW of Ethanolic corn silk (Zea mays L) extract showed significant analgesic activity (p<0.05). In general, the data obtained from the present study elucidated that the extract possessed significant analgesic activities and recommended for further studies to determine the mechanism of action and toxicity.